Application of LEAN tool "line balancing" to determine the productivity of workforce in activities of plastering and internal detailing in two-story houses made of masonry (2018)
The finishing work of construction represents an aggregated value that makes the difference when a client is deciding to buy a house. The stipulated costs for plastering and detail activities for houses, in occasions, surpasses 30% of the total value of the construction work, considerable costs that require constant control and supervision both in the analysis and the execution of the construction. The implementation of the LEAN philosophy in this activity is not commonly implemented due to the lack of knowledge of the tools that this method provides. This research shows the implementation of line balancing, as a LEAN tool, in the plastering and detailing activities for two-story masonry houses, constructed in the housing project Callejas del Este which took place in the city of Cucuta, Colombia. The implementation of this tool contemplated the analysis of execution times of the work crew, the results were synthesized in tables for better interpretation and conclusions of interest were developed for the improvement of the observed processes and activities.